2007
DOI: 10.1128/mcb.00523-07
|View full text |Cite
|
Sign up to set email alerts
|

GDI-1 Phosphorylation Switch at Serine 96 Induces RhoA Activation and Increased Endothelial Permeability

Abstract: We identified the GDI-1-regulated mechanism of RhoA activation from the Rho-GDI-1 complex and its role in mediating increased endothelial permeability. Thrombin stimulation failed to induce RhoA activation and actin stress fiber formation in human pulmonary arterial endothelial cells transduced with full-length GDI-1. Expression of a GDI-1 mutant form (C-GDI) containing the C terminus (aa 69 to 204) also prevented RhoA activation, whereas further deletions failed to alter RhoA activation. We observed that prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 36 publications
(86 reference statements)
6
81
2
Order By: Relevance
“…It has also been shown that some PKC isozymes, such as PKCa, could activate RhoA by inducing rapid phosphorylation of GDP dissociation inhibitor (GDI), indicating that RhoA would be one of the important substrates of PKC. 45,46 Our previous study also suggested that NOS was a potent substrate of PKC, while inhibition of nitric oxide synthase (NOS) with specific blocker NG-monomethyl-L-arginine (L-NMMA) greatly attenuated the hyperpermeability effect of PMA, indicating that PKC may alter endothelial permeability by directly acting on endothelial structural proteins and/or indirectly by modulating activity of common signaling protein NOS, as can be seen in Fig. 8B.…”
Section: Protein Kinase C Plays a Role In Vascular Permeability Regulmentioning
confidence: 85%
See 1 more Smart Citation
“…It has also been shown that some PKC isozymes, such as PKCa, could activate RhoA by inducing rapid phosphorylation of GDP dissociation inhibitor (GDI), indicating that RhoA would be one of the important substrates of PKC. 45,46 Our previous study also suggested that NOS was a potent substrate of PKC, while inhibition of nitric oxide synthase (NOS) with specific blocker NG-monomethyl-L-arginine (L-NMMA) greatly attenuated the hyperpermeability effect of PMA, indicating that PKC may alter endothelial permeability by directly acting on endothelial structural proteins and/or indirectly by modulating activity of common signaling protein NOS, as can be seen in Fig. 8B.…”
Section: Protein Kinase C Plays a Role In Vascular Permeability Regulmentioning
confidence: 85%
“…As mentioned above, RhoA might be one of the important substrates of PKC. 44,45 These data re-stress the pivotal role of Rho/ROCK pathway in the modulation of endothelial barrier function. In contrast, while PKC also restrained the formation of stress fiber in burned-serum treated endothelial cells, the inhibition of PKC with Ro-31-7549 did not attenuate the phosphorylation of p38 after burned plasma administration, implying the p38-independent effect of PKC on endothelial morphological regulation.…”
Section: Protein Kinase C Plays a Role In Vascular Permeability Regulmentioning
confidence: 94%
“…In addition, both yeast and mammalian eIF5 have been shown to be phosphorylated by Casein Kinase II. 37,38 While regulation by phosphorylation has been demonstrated for a number of other GDIs [39][40][41] it is not yet clear if eIF5-GDI is regulated by changes in post-translational modification.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…2,12,17 In an unperturbed endothelium, IEJs dynamically open to allow the passage of small molecules and inflammatory cells for tissue homeostasis and immune surveillance. 2,8,9,12,14 Proinflammatory agonists such as thrombin, vascular endothelial growth factor (VEGF), and platelet-activating factor, [19][20][21][22] by binding to their receptors, disorganize IEJs, leading to increase in endothelial permeability. Thus, to understand how tissue-fluid homeostasis is modulated under normal conditions and pathological processes, we must understand the signaling mechanisms that regulate IEJs.…”
mentioning
confidence: 99%